Tanggung Jawab Wali Amanat Kepada Pemegang Obligasi Dalam Hal Wali Amanat Melakukan Kelalaian Terhadap Kontrak Perwaliamanatan - Pangihutan, Kaiji Natanael; Abubakar, Lastuti; Rahmawati, Ema (Fakultas Syariah INSURI Ponorogo, 2023)
The trustee is the party responsible for assisting the implementation of bond issuance and transactions in the capital market. In the implementation of bond issuance, the role of the trustee is crucial in creating legal protection for bondholders. The purpose of this study is to clearly understand the duties and responsibilities of the trustee towards bondholders as well as the legal protection rights possessed by bondholders if the trustee commits acts of negligence under capital market law. The results showed that the trustee must make compensation as a form of legal protection to bondholders in accordance with the regulations contained in the laws and regulations in the field of capital market and bondholders who feel aggrieved can ask the trustee for compensation by means of consensus deliberation or dispute resolution at an alternative dispute resolution institution established by the Service Authority Finance (OJK). Bondholders can also prove to court because the losses suffered are the result of the negligence of the trustee who represents them in a bond issuance process.